2018
DOI: 10.1021/acs.jmedchem.7b01691
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Based Drug Discovery of Inhibitors of Phosphopantetheine Adenylyltransferase from Gram-Negative Bacteria

Abstract: The discovery and development of new antibiotics capable of curing infections due to multidrug-resistant and pandrug-resistant Gram-negative bacteria are a major challenge with fundamental importance to our global healthcare system. Part of our broad program at Novartis to address this urgent, unmet need includes the search for new agents that inhibit novel bacterial targets. Here we report the discovery and hit-to-lead optimization of new inhibitors of phosphopantetheine adenylyltransferase (PPAT) from Gram-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 80 publications
(48 reference statements)
3
34
0
Order By: Relevance
“…About 37 statistically positive hits (Supplementary figure 2), which represent about 2.8% of the library with significant chemical diversity, were identified when screened at a fragment concentration of 10 mM. This hit rate is similar to that obtained in several other FBDD campaigns 27,44,24 . The remaining molecules of the library did not significantly stabilise the MtDHFR or displayed a negative ΔTm, indicating a stabilisation of the unfolded state of MtDHFR, consequently, these molecules were also not considered for further analysis.…”
Section: Screening By Dsf and Validation By 1d Std-nmrsupporting
confidence: 75%
“…About 37 statistically positive hits (Supplementary figure 2), which represent about 2.8% of the library with significant chemical diversity, were identified when screened at a fragment concentration of 10 mM. This hit rate is similar to that obtained in several other FBDD campaigns 27,44,24 . The remaining molecules of the library did not significantly stabilise the MtDHFR or displayed a negative ΔTm, indicating a stabilisation of the unfolded state of MtDHFR, consequently, these molecules were also not considered for further analysis.…”
Section: Screening By Dsf and Validation By 1d Std-nmrsupporting
confidence: 75%
“…Hydrogen bonding interactions with the indicated active site residues are shown as black dashed lines. (C) Inhibitors of E. coli and P. aeruginosa PPAT displaying sub-micromolar activity (Moreau et al, 2018). (D) Selective inhibitors of MtPPAT identified through in silico screening, which are predicted to prevent substrate binding at the active site (Podshivalov et al, 2017).…”
Section: Coad -Phosphopantetheine Adenylyltransferase (Ppat)mentioning
confidence: 99%
“…While no inhibitors have been reported for MtPPAT using structure-based approaches, inhibitors have been described for EcPPAT, its homologue from E. coli (Zhao et al, 2003;Miller et al, 2010;Moreau et al, 2018;Skepper et al, 2018;Liyanage et al, 2019;Wang et al, 2020). The two homologues share 44% identity and 77% similarity in their amino acid sequences, and both exist as hexamers in their active form (Timofeev et al, 2010).…”
Section: Ppat Inhibitors Developed Through Rational Designmentioning
confidence: 99%
See 1 more Smart Citation
“…90 A research group from Novartis has identified inhibitors of gram-negative bacterial PPAT using an FBLG approach. 91 All fragment hits bind at the 4′-phosphopantetheine site of Escherichia coli PPAT. Lead compounds 23a and 23b ( Fig.…”
Section: New Structures For Old Molecular Targets: “A Good Target Is mentioning
confidence: 99%